Evolution of impatience: The example of the Farmer-Sheriff game - Levine, David K. (2015)
The literature on the evolution of impatience, focusing on one-person decision problems, often finds that evolutionary forces favor the more patient individuals. This paper shows that in games where equilibrium involves threat of punishment there are forces generating an evolutionary advantage to the impatient. In particular, it offers a two-population example where evolutionary forces favor impatience in one group while favoring patience in the other. Moreover, efficiency may also favor impatient individuals. In our example, it is efficient for one population to evolve impatience and for the other to develop patience. Yet, evolutionary forces move the opposite direction.